Pendampingan Penyusunan Standar Operasional Prosedur (SOP) Pengembangan Program Bapak Angkat Dinas PPKUKM DKI Jakarta - Susanto, Tri; Novianti, Mirsa Diah; Budipriyanto, Adi (LPkM Universitas Bakrie, 2022)
This assistance activity in the preparation of Standard Operating Procedures (SOP) of Foster Father's Program a community service activity that aims to produce a draft SOP of Foster Father's Program at the Industry and Trade Office of Small and Medium Enterprise Cooperatives (PPKUKM) of DKI Jakarta Province, as well as improving understanding related to the theory, principles, and techniques for preparing SOP in accordance with government regulations. A SOP is a written manual. Participants of this activity came from 5 private universities in Jakarta and one of them was Bakrie University which together with the PPKUKM Office actively participated in the SOP development socialization event in March 2021 using mentoring methods. The activity of preparing the SOP for the Development of Foster Father's Program begins with the activity of compiling and collecting materials, after which the material or material activities, then continued by formulating the Operational Standard of The Development Procedure of Development Foster Father's Program.